The Evaluation of Some Biomarkers According to Rheumatoid Factor in Early Diagnosis of Rheumatoid Arthritis from Iraqi Patients - Hassoon, Hind Jaber; Jasim , Walaa Esmail; Abbas , Ahmed Abdul Hassan (Iraqi Journal of Science, 2020)
Rheumatoid arthritis (RA) was a chronic inflammatory autoimmune disease for long-term that primarily affects small joints and leads to chronic inflammation in synovial. The aimed of the study to identify the relationships among some serological markers (antibodies to citrullinated protein/peptide antigens (ACPAs), anti-mutated citrullinated vimentin (anti-MCV), anti-carbamylated protein (Anti-Carp), anti- heterogeneous nuclear ribonucleoproteins (anti-hnRNP) and Glucose-6-phosphate isomerase (GPI)) and early diagnosis of RA. The study involved (60) Patients of newly diagnosis with RA that divided in to two subgroups (30 RF positive and 30 RF negative) groups and 30 subjects as healthy control group. The serological data from serum concentration of (ACPAs, Anti-MCV, Anti-Carp, Anti-hnRNP, G6PI) estimated by ELISA methods, RF estimated by latex agglutination kits. The results revealed that ACPAs, Anti-MCV, Anti-Carp, Anti-hnRNP, G6PI having a statistical significants at the meanÂ±SD titer different between the two RF groups, a higher value among the refractory RA patients in comparison with the control group. Also effectively distinguishing RA patients groups for RF+ve and RF-ve with showed the sensitivity and specificity of, ACPAs (90.8% , 94.1%, and 88.2%, 86.6%); anti-MCV (66.7% , 33.0% and 70.0%, 70.2%); anti-CarP (76.7% , 90.0% and 93.3%, 78.5%); anti-hnRNP (74.9% , 61.9% and 71.4%, 70.9%) and GPI (77.3% , 76.7% and 84.4%, 80.1%) respectively. This study confirm the importance of measuring multiple serum biomarkers and their comÂbinations with high diagnostic value for RA and provide supÂport for the early diagnosis of RA.